2021
DOI: 10.1017/cjn.2021.122
|View full text |Cite
|
Sign up to set email alerts
|

Ketonuria and Seizure Control in the Medium Chain Triglyceride and Classic Ketogenic Diets

Abstract: We hypothesized that children receiving medium-chain triglyceride ketogenic diet (MCTKD) experience similar seizure reduction despite lower ketosis compared with classic ketogenic diet (CKD). Children initiating CKD or MCTKD were enrolled in a prospective observational study. Forty-five children completed 6 months of KD (n = 17 MCTKD, n = 28 CKD). The proportion achieving ≥50% seizure reduction was 71% CKD group and 59% MCTKD group; ≥90% reduction was 32% and 36% in CKD and MCTKD groups, respectively. CKD had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In another study comparing the efficacy of the MAD and classic KD, blood β‐OHB levels did not correlate with seizure control in either group. Finally, Lowe et al 28 demonstrated that although patients receiving the MCT KD had lower urine ketones than those on the classic KD, seizure outcomes were similar.…”
Section: Does the Ketogenic Ratio And The Degree Of Ketosis Influence...mentioning
confidence: 99%
“…In another study comparing the efficacy of the MAD and classic KD, blood β‐OHB levels did not correlate with seizure control in either group. Finally, Lowe et al 28 demonstrated that although patients receiving the MCT KD had lower urine ketones than those on the classic KD, seizure outcomes were similar.…”
Section: Does the Ketogenic Ratio And The Degree Of Ketosis Influence...mentioning
confidence: 99%
“…In addition, there was a reduction in seizure frequency by 90% or more in 32 and 36% of patients in the CKD and MCTKD groups, respectively. Although the CKD group had higher urine ketones, the MCTKD group experienced similar seizure control despite lower urine ketone levels [19]. Studies in children with drug-resistant epilepsy on the ketogenic diet have indicated that ketosis can result in reducing brain's oxidative stress by increasing beta hydroxybutyrate and arachidonic acid [33].…”
Section: Indications For the Use Of Ketogenic Diet Therapy And The Ro...mentioning
confidence: 97%
“…The higher ketogenic potential of MCT provides a more liberal alternative to the classic ketogenic diet, paving the way to improving tolerability in patients on dietary therapy. This diet is prescribed as a percentage of macronutrients with total fat intake starting at 71% of total daily caloric intake, 40–50% of which is from MCT oil [19]. Similar results in seizure freedom when compared with the classic ketogenic diet are thought to result from a potential anticonvulsant effects of medium chain fatty acids such as caprylic acid and capric acid [19].…”
Section: Medium Chain Triglyceride Dietmentioning
confidence: 99%
See 2 more Smart Citations